2018
DOI: 10.1245/s10434-018-6729-6
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcome Measures May Add Value in Breast Cancer Surgery

Abstract: PRO scores were associated with age, time since surgery, type of surgery, and radiation therapy in breast cancer patients. The scores serve as a reference value for different types of surgery in the study population and enable prospective use of PROs in shared decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
42
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 20 publications
(24 reference statements)
7
42
0
2
Order By: Relevance
“…The domain "Sexual Well-being" had a markedly lower median score of 58 and, furthermore, the response rate was low at 69.6%. This pattern has also been seen in previous studies investigating BCT [8,9,36], and it seems to be a general issue for this domain. Therefore, results must be interpreted with caution.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The domain "Sexual Well-being" had a markedly lower median score of 58 and, furthermore, the response rate was low at 69.6%. This pattern has also been seen in previous studies investigating BCT [8,9,36], and it seems to be a general issue for this domain. Therefore, results must be interpreted with caution.…”
Section: Discussionsupporting
confidence: 86%
“…In the domain "Psychosocial Well-being" we found a median score of 82, similar to the results of O´Connell [8] and Dahlbäck [35], using Breast-Q™ for evaluation of the outcome of BCT, while Langendiik [36] found a mean score at 70.1 and Vesprini [9] found a mean score at 73.5. In our study we found a statistically significant better outcome for the OBS cohort, including level I and II surgery, compared with the BCS cohort.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…PRO measures have gained traction as components of value-based health care decision making, including in assessment of comparative effectiveness and shared decision-making support in areas such as breast cancer surgery. 19,20 There is even discussion of third-party payers incorporating PRO data into valuebased reimbursement schemes. 21 Standardized tools incorporating patients' perspectives have been developed and validated to assess QoL for patients with many conditions.…”
Section: Developing a Standardized Instrument For Ftmentioning
confidence: 99%